2016
DOI: 10.1080/03014460.2016.1189963
|View full text |Cite
|
Sign up to set email alerts
|

Immune function in Amazonian horticulturalists

Abstract: Background Amazonian populations are exposed to diverse parasites and pathogens, including protozoal, bacterial, fungal, and helminthic infections. Yet much of our understanding of the immune system is based on industrialised populations where these infections are relatively rare. Aim We examine distributions and age-related differences in 22 measures of immune function for Bolivian forager-horticulturalists and US and European populations. Subjects and Methods Subjects were 6,338 Tsimane aged 0–90 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
131
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 90 publications
(139 citation statements)
references
References 84 publications
1
131
2
Order By: Relevance
“…On average, 20% of WBCs are eosinophils, also indicative of intense parasitic infection, compared with the normal US reference range of <5%, with >90% of Tsimane adults in the clinically high range. Natural killer cells and B cell counts are approximately twice as high as typical US values (Blackwell et al 2016). Tsimane also demonstrate higher levels of inflammation than those found in industrialized populations.…”
Section: Methodsmentioning
confidence: 75%
See 2 more Smart Citations
“…On average, 20% of WBCs are eosinophils, also indicative of intense parasitic infection, compared with the normal US reference range of <5%, with >90% of Tsimane adults in the clinically high range. Natural killer cells and B cell counts are approximately twice as high as typical US values (Blackwell et al 2016). Tsimane also demonstrate higher levels of inflammation than those found in industrialized populations.…”
Section: Methodsmentioning
confidence: 75%
“…The costs of immune activation can be substantial: Tsimane adults with clinical symptoms of intestinal helminth infection have excess RMR of 116-138 kcals/d (Table S4). Elevated WBC counts are 10 times more prevalent among Tsimane than Americans; Tsimane WBCs are 2,600 cells/uL higher on average than US levels among adults age 18-49 (Blackwell et al 2016), which in our model adds 23-28 excess RMR kcals/day. These findings build upon results from studies in Western populations showing RMR increases with infection (Muehlenbein et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal helminths are lipophilic and absorb lipids either from their host’s gut contents or blood stream, either of which could reduce their host’s circulating lipids and thereby minimize accumulation of plaques in vasculature [36]. Additionally, endo-parasites like helminths represent a significant energetic cost from immune activation that increase resting metabolic rates, further limiting adipose tissue deposition [37, 38]. These helminths were likely a prevalent source of infection over human evolutionary history.…”
Section: Introductionmentioning
confidence: 99%
“…The authors noted the limited number of studies on these kinds of groups and call for additional research and public health policies to improve their qualityof-life and health. Blackwell et al (2016) address the complex issue of how the human immune system responds to rural Amazonian environments. They examined 22 measures of immune function and found that Tsimane' of all age groups show elevations in most measures of immune function in comparison to reference populations.…”
Section: Human Biology Of the Amazonmentioning
confidence: 99%